Dynamics of respiratory system clinicofunctional scores among patients with COPD in the complex rehabilitation at the Health resort Belokurikha - K. V. Komissarov; Ye. V. Viktorova; G. V. Trubnikov (Бюллетень сибирской медицины)
The aim of the study was to estimate the dynamics of respiratory system clinicofunctional scores among patients with COPD at the health resort Belokhuriha. There were examined 188 cases of mild and middle-severe COPD. All the patients received different rehabilitation complexes in the conditions of health resort Belokuriha’s climate-recreational zone against the background of which there was conducted an estimation of the respiratory system clinicofunctional scores and depending on the applied methods there was evaluated its efficiency. In the process of the group rehabilitation where physical exercises were included there was recorded the dynamics of the main symptoms — decrease of the manifestation degree of dyspnea, cough, sputum discharge and scores of the respiratory system functional tests. OFV1 has reliably increased only in the group where clipping massage, exercises in the counter-resistance mode for the respiratory muscles and the terrainkur were used. The use of physical exercises in the rehabilitation of patients with COPD improves clinicofunctional scores of the respiratory system and its efficiency.